Does calprotectin level identify a subgroup among patients suffering from irritable bowel syndrome? Results of a prospective study. Issue 2 (1st March 2017) - Melchior, Chloé; Aziz, Moutaz; Aubry, Typhaine; Gourcerol, Guillaume; Quillard, Muriel; Zalar, Alberto; Coëffier, Moïse; Dechelotte, Pierre; Leroi, Anne‐Marie; Ducrotté, Philippe
Abstract : Background: Irritable bowel syndrome is a multifactorial disease. Although faecal calprotectin has been shown to be a reliable marker of intestinal inflammation, its role in irritable bowel syndrome remains debated. Objective: The aims of this prospective study were to select a subgroup of irritable bowel syndrome patients and to characterise those patients with high faecal calprotectin by systematic work‐up. Methods: Calprotectin levels were determined by enzyme‐linked immunosorbent assay test in consecutive irritable bowel syndrome patients fulfilling Rome III criteria in whom normal colonoscopy and appropriate tests had excluded organic disease. Calprotectin levels were compared in irritable bowel syndrome patients, healthy controls and patients with active and quiescent Crohn's disease. When the calprotectin level was higher than 50 µg/g, the absence of ANCA/ASCA antibodies and a normal small bowel examination were required to confirm irritable bowel syndrome diagnosis. Additional explorations included assessment of irritable bowel syndrome severity, anxiety and depression, impact on quality of life, glucose and fructose breath tests, rectal distension test by barostat and quantitative and qualitative assessment of inflammation on colonic biopsies. Results: Among the 93 irritable bowel syndrome patients (73% women; 66.7% with diarrhoea) recruited, 34 (36.6%) had reproducibly elevated calprotectin. Although they tended to be older than those with normal calprotectin ( P = 0.06), there were no other differences between the two groups. When elevated, calprotectin was correlated with age ( P = 0.03, r = 0.22). Conclusions: Elevated faecal calprotectin was observed in one third of patients in this series, without any significant association with a specific clinical phenotype (except age) or specific abnormalities.